DIFFERENCES OF MASS AND DIAMETER MUSCLE RATTUS NORVEGICUS IN GIVING KETOGENIC DIETS AND EXERCISE - Danika, Andri; Dewi, Dewa AL; Sindrawati, Sindrawati (JOURNAL OF WIDYA MEDIKA JUNIOR, 2021)
Introduction: Saturated ketogenic diet without exercise can lead to muscle mass decrease and disturb body metabolism. Therefore, the researcher is interested in discovering the differences between a saturated and unsaturated ketogenic diet with exercise to muscle mass and diameter. Purpose: This study aimed to analyze the difference in muscle mass and diameter of Rattus norvegicus, which were given a ketogenic diet and exercise. Method: This experimental research used Rattus norvegicus that had been adapted for two weeks. Rats are divided into five groups; control (K), a saturated ketogenic diet (P1), a saturated ketogenic diet with exercise (P2), an unsaturated ketogenic diet (P3), and anunsaturated ketogenic diet with exercise (P4). Upright running wheel exercise was given to the group with exercise for 10 minutes daily. The ketogenic diet was given with oral gavage. Muscle mass was examined in the second and fourth weeks. Muscle diameter was examined before treatment, second week, and fourth week. Results: There are differences in mass and diameter muscle Rattus norvegicus that givenketogenic diet and exercise (p=0,000). In second week, there are significant increase inmuscle diameter for saturated ketogenic diet without exercise (P1(p=0,000)) and significantdecrease in muscle diameter for three other group (P2(p=0,000), P3(p=0,001), P4(p=0,000)). In the fourth week, there is a significant increase in muscle diameter for an unsaturated ketogenic diet with exercise (P4). Conclusion: An unsaturated ketogenic diet with exercise could increase the mass anddiameter of quadriceps muscle at the end of this research.